Server information mechanism in a discrete-time queueing system - Atencia-McKillop, Iván; Galán-García, José Luis; Aguilera-Venegas, Gabriel; Rodríguez-Cielos, Pedro; Galán-García, María Ángeles (My University, 2018)
This paper discusses a discrete-time queueing system in which an arriving customer may adopt four di erent strategies depending on the income information, two of them correspond to a LCFS discipline where displacements or expulsions occur, and in the other two, the arriving customer decides to follow a FCFS discipline or to become a negative customer eliminating the customer in the server, if any. The di erent choices of the involved parameters make this model to enjoy a great versatility, having several special cases of interest.
Keywords: Sistemas de tiempo discreto